The slack test does not assess maximal shortening velocity of muscle fascicles in humans - Hager, R.; Dorel, S.; Nordez, A.; Rabita, G.; Couturier, A.; Hauraix, H.; Duchateau, J.; Guilhem, G. (The Journal of Experimental Biology, 2018)
The application of a series of extremely high accelerative motor-driven quick releases while muscles contract isometrically (i.e. slack test) has been proposed to assess unloaded velocity in human muscle. This study aimed to measure gastrocnemius medialis fascicle shortening velocity (VF) and tendinous tissue shortening velocity during motor-driven quick releases performed at various activation levels to assess the applicability of the slack test in humans. Gastrocnemius medialis peak VF and joint velocity recorded from 25 participants using high frame rate ultrasound during quick releases (at activation levels from 0% to 60% of maximal voluntary isometric torque) and during fast contractions without external load (ballistic condition) were compared. Unloaded joint velocity calculated using the slack test method increased whereas VF decreased with muscle activation level (P=0.03). Passive and low-level quick releases elicited higher VF values (=41.8±10.7 cm s-1) compared with the ballistic condition (36.3±8.7 cm s-1), while quick releases applied at 60% of maximal voluntary isometric torque produced the lowest VF. These findings suggest that initial fascicle length, complex fascicle-tendon interactions, unloading reflex and motor-driven movement pattern strongly influence and limit the shortening velocity achieved during the slack test. Furthermore, VF elicited by quick releases is likely to reflect substantial contributions of passive processes. Therefore, the slack test is not appropriate to assess maximal muscle shortening velocity in vivo.